Malignant eccrine spiradenoma with carcinomatous and sarcomatous elements. Issue 10 (October 1997) - McCluggage, W G; Fon, L J; O'Rourke, D; Ismail, M; Hill, C M; Parks, T G; Allen, D C
Abstract : A case of a 60 year old man with malignant eccrine spiradenoma involving the perineum is described. Areas of typical eccrine spiradenoma were admixed with carcinomatous and sarcomatous elements. Immunohistochemical and ultrastructural analysis revealed no evidence of epithelial differentiation in the sarcomatous areas. The tumour qualified for the designation carcinosarcoma arising in eccrine spiradenoma. The clinical course was aggressive with rapid development of nodal and pulmonary metastases.